Análisis de la calidad trófica del embalse el Hato (2018)
In this article the analysis of the trophic quality of the El Hato reservoir is presented, based on the information available for contributions of phosphorus to the reservoir. Additionally, the general characteristics and antecedents of the reservoir, the experimental information of the charges and phosphorus concentrations on the reservoir necessary to evaluate its trophic condition are indicated, and finally, the application of the Vollenweider model and its analysis.